External Debt Dynamics and Sustainable Growth in Nigeria - Ndubuaku, Victor Chijioke; Uche, Michael Ugochukwu; Onwuka, Cynthia Chika; Ifeanyi, Patricia Ozioma (International Journal of Sustainable Development & World Policy, 2021)
The paper provides empirical insights about how the interactions between the external debt and external sector dynamics impacts on economic growth in Nigeria. The paper underscored the critical desire to understand how debt-growth relationship could be optimized for sustainable economic development and growth in developing countries. It proposes modelling the external sector and debt dynamics in order to attain sustainable development in Nigeria. This study became imperative because Nigeria occupies a very significant position in Africa. Nigeria, though a developing country, is currently the largest black nation in the world and most populous country in Africa. The paper opted for an ex post facto research design using CBN statistics extrapolated from its statistical bulletin with 37year coverage from1980-2016. The data was analyzed using the ARDL and granger causality technique coupled with other pre-estimation and diagnostic tests. The result showed foreign-debt and debt-service was negatively not-significant on sustainable growth. It was concluded that though Nigeria wasn’t wrongly positioned on the debt-laffer-curve, the economy had not benefitted positively from the mass of debt funds accessed. The paper’s primary contribution is finding that external debt and debts service had a negative (not-significant) impact on economic growth in Nigeria. The policy implication of this research may be applied to other developing countries. The propositions may however lack general applicability in more advanced economies.